Metode Umat Wasatîyah dalam al-Qur’an - Mu'tasim Hasan, Muzayyanah (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2011)
Interpretation’s study constantly faced with the difficulty of how to gain a thorough understanding (holistic) and avoid refractive understanding, the lack of continuity (matching) between the norms of Islam that is very noble to the reality of Muslim who are not “Islamic” what causes that to happen? Is an understanding of aspects of Islam has ceased and focus on long heritage (turâth) this is no longer considered to be the actual state of time, or because the understanding of Islam was viewed as a textual only, so it’s resulting in an antagonistic attitude of Muslims and puritans! This article attempts to answer these questions.